Corrections to "Unsupervised Anomaly Detection of Industrial Robots Using Sliding-Window Convolutional Variational Autoencoder" - Chen, Tingting; Liu, Xueping; Xia, Bizhong; Wang, Wei; Lai, Yongzhi (IEEE access, 2020)
Presents corrections to the above mentioned paper.